КОНЦЕПЦІЯ «ПОЛІГРАФА ШАРІКОВА»: ПРОБЛЕМНІ ПИТАННЯ ОНОВЛЕННЯ ЦИВІЛЬНОГО ЗАКОНОДАВСТВА УКРАЇНИ - Koverznev, V.O. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2021)
The article substantiated that by its legal nature the Concept of updating the Civil Code of Ukraine reflects exclusively the personal views of a small group of scientists, the authenticity of which is not confirmed by the results of scientific research; the document does not have the status of a scientific publication and has not passed the procedure for discussion in the professional environment. The private nature of the Concept preparation excludes its use as a basis for legislative work of the Verkhovna Rada of Ukraine. It has been proved that the Concept has methodological problems, and the proposals formulated in it contradict the Constitution of Ukraine, violate social guarantees and do not agree with the norms of the current legislation, in particular: the Law of Ukraine “On Local Self-Government in Ukraine”, the Tax Code of Ukraine, the Land Code of Ukraine, the Law of Ukraine “On Education”, the Law of Ukraine “On Protection of Economic Competition” etc. It was emphasized that the implementation of certain provisions of the Concept for updating civil legislation of Ukraine will lead to the impossibility of practical implementation by local self-government bodies of functions in the field of housing and communal services, consumer services; in the field of culture, health, education, physical education and sports and the commercialization of these services. This will lead to a rapid increase in the level of prices for housing and communal services, the complete destruction of the system of free medical care, as well as free preschool, complete general secondary and professional (vocational) education. Since more than 60% of the population of Ukraine is currently below the poverty line, a significant increase in prices for utilities, the transfer of healthcare institutions, as well as preschool, general secondary and vocational (vocational) education exclusively on the commercial basis of management will deprive the vast majority of the population of the financial opportunity to pay their market value, which will lead to a further decrease in living standards and deterioration of the demographic situation in Ukraine, which is already unsatisfactory. In addition, the population of Ukraine will be limited in access to the services of cultural, physical education and sports institutions. It was concluded that the refusal of the real right of economic management and the right of operational management will create preconditions for depriving territorial communities of communal property and the impossibility of fulfilling their constitutional powers, as well as to enrich a small group of persons of private law and the final impoverishment of the rest of the population of Ukraine. REFERENCES 1. Kontseptsiia rekodyfikatsii Tsyvilnoho kodeksu Ukrainy. URL: https://drive.google.com/file/d/1ExwdnngsmvpAZJtWi836Rr6-x1quaZJQ/view [in Ukrainian].